Predictors of academic engagement of high school students: academic socialization and motivational beliefs - Getachew Tassew Woreta (Frontiers in Psychology, 2024)
The potential of academic engagement to enhance academic outcomes and well-being has been empirically supported, yet studies addressing its predictors are too limited. Hence, the current study collected self-report cross-sectional data from randomly selected 614 (male = 323) high school students in Ethiopia and examined the relations of academic socialization (parental and peer), self-efficacy, and outcome expectations in explaining variance in academic engagement, guided by an integrative model of engagement. Structural equation modeling with the maximum likelihood method indicated that (a) the hypothesized model fit the data well, (b) direct paths from parental and peer academic socialization to self-efficacy, outcome expectations, and academic engagement were positive and significant, (c) the relationships of the constructs in the model explained a significant portion of the variance in academic engagement, and (d) self-efficacy and outcome expectations significantly and positively but partially mediated the pathway from academic socialization to academic engagement. The findings’ implications for boosting student academic engagement were forwarded.